秦刻石李斯书法研究 - 刘, 晓曼 (2023)
李斯为秦朝政治家、文学家和书法家。其少为郡吏，曾从荀卿学，因其在“书同文”背景下出色的书法创作成就和影响，东晋王羲之、宋代羊欣等论述主张李斯开创了中国书法创作先河，称其为“书家第一人”。关于李斯的书法定位问题，目前尚存在着一些不全面的观点。论文尝试从李斯书法创作在“书同文”背景下对秦政权巩固、中国文字史、中国书法史等方面的影响角度出发，展开研究。 论文从秦统一六国，结束诸侯国各自为政的历史背景入手，讨论在“书同文”背景下李斯书法的创作。笔者结合历代古籍及现当代学者著书中对“书同文”政令、“李斯书法”等的记载与点评，讨论得出“书同文”推行的效果，引出李斯书法在此过程中产生的影响。 随着秦统一六国的发展，社会亟需一种思想文化纽带来带领及教化民众，文字就是沟通思想文化的重要载体及渠道。李斯书法作为官方文字出现在秦皇权彰显产物——秦诏版、阳陵虎符、秦刻石等之上，是值得探究和讨论的。同时，该书体对于秦政权巩固的作用及影响也是值得整理、分析和考究的。在对李斯书法作品的整理过程中，自然地呈现出汉字的演变过程。通过表格对比分析，发现李斯笔下书体的存在，是中国汉字演变过程中重要的过渡环。同时，其书体的造型也在“去象形化”的过程中彰显着对文字“造型美”的追求，这是汉字走向书法艺术的有力证明。由此分析，从中国文字史发展的角度分析，李斯书法是“古文字”与“今文字”承上启下的重要见证。从中国书法史的角度分析，李斯书法也启蒙了汉字向书法文化的发展。论文研究过程中，由浅入深，发现李斯书法的种种影响均构建在秦“书同文”背景下。文章运用文献研究法、比较分析法、图文互证法、多学科交叉研究法等研究方法分析“李斯书法”的创作及影响，力求新义新论。Li Si was a statesman, writer, and calligrapher of the Qin Dynasty. Li Si was a county official and studied from Xun Qing. Because of his outstanding achievements and influence in calligraphy creation under the background of "Shu Tong Wen", Wang Xizhi of the Eastern Jin Dynasty, and Yang Xin of the Song Dynasty, etc. indicated that Li Si created a precedent for Chinese calligraphy creation, and as he "the first person to create Chinese calligraphy". There are still some incomplete views on Li Si's calligraphy orientation. Under the background of "Shu Tong Wen", the thesis attempts to conduct research from the perspective of the influence of Li Si's calligraphy creation on the consolidation of the Qin regime, the history of Chinese writing, and the history of Chinese calligraphy. The thesis starts from the historical background of Qin unifying the six countries and ending the country's divided, and discusses the creation of Li Si's calligraphy under the background of "Shu Tong Wen". The author combines the records and comments on the "Shu Tong Wen" and "Li Si's calligraphy" from the ancient books of the past dynasties and the books of modern and contemporary scholars. And then, discuss the effect of the implementation of "Shu Tong Wen", prove the influence onLi Si's calligraphy in this process. With the development of Qin's unification of the six countries, society urgentlyneeds an ideological and cultural bond to lead and educate the people, and words writing is an important carrier and channel for communication of ideology and culture. Li Si's calligraphy, as the official text, appeared on the products of Qin's imperial power - Qin Zhao version, Yangling tiger talisman, Qin carved stone, etc. It is worthexploring and discussing. At the same time, the role and influence of the book style on the consolidation of the Qin regime is also worthy of sorting, analysis, and research. In the process of arranging Li Si's calligraphy works, the evolution of Chinese characters was presented. Through the comparative analysis of the tables, it is foundthat the existence of the calligraphy written by Li Si. This is an important transitional link in the evolution of Chinese characters. At the same time, the shape of its calligraphy also shows the pursuit of "beautiful shape" in the process of "de- pictographic", which is strong proof that Chinese characters are moving towards calligraphy art. From the perspective of the development of Chinese writing history, Li Si's calligraphy is an important testimony to the connection between "ancient writing" and "modern writing". From the perspective of Chinese calligraphy history, Li Si's calligraphy also enlightened the development of Chinese characters in calligraphy culture. In the process of the research of the thesis, from the simple to the deep, it is found that the various influences of Li Si's calligraphy are all constructed under the background of "Shu Tong Wen". The article analyzes the creation and influence of "Li Si's Calligraphy" utilizing the literature research method, comparative analysis method, picture-text mutual proof method, multi-disciplinary research method, andother research methods, and strives for new meanings and new theories.